(untitled) (Fiep Bulletin - online, 2015)
The main goal of this research consisted of the analysis of the ANS before and after the work of employees in different turns, verifying the levels of stress. The sample was composed for 27 employees divided in three turns of the sector of production of a company, of the masculine sex with ages between 25 and 45 randomly. The analysis was carried through the Bioexpress program that identifies, from data of the cardiac electrophysiology, the ideal levels of the sympathetic and parasympathetic nervous system that compose the autonomous nervous system. Applied the Epworth Sleep Scale as a coadjutant diagnosis. The observed results had been that the level of the SNS was presented higher in the first examination in all the employees disclosing a bigger level of stress before working. The PNS was higher in as the examination in all the employees disclosing the ANS after working (homeostasis). However, the increase of the sympathetic activity before work can be considered light translating the state of eustress (good stress or physiological). The Sleep Scale showed that the majority of the employees have good quality of sleep or is in the acceptable limit. Ahead of these results it was perceived that the work environment did not cause an increase of the stress and that sleep was not the main cause of the increase of the activity of the SNS before work concluding that the work leads to an alteration in the levels of SNS and PNS, however nor always this alteration is worse.